2018
DOI: 10.1002/jmv.25267
|View full text |Cite
|
Sign up to set email alerts
|

Advanced liver fibrosis effects on the response to sofosbuvir‐based antiviral therapies for chronic hepatitis C

Abstract: Both older and younger patients respond similarly to DAA therapy. Advanced liver fibrosis affects the virological response to sofosbuvir-based therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The antiviral effect of DAAs is lower for patients with cirrhosis compared to patients with chronic hepatitis. 18 Among the patients with cirrhosis, patients with decompensated cirrhosis have a lower susceptibility to DAA therapy compared to those with compensated cirrhosis. 19 The SVR12 rate in this study was 85% (28 of 33 patients) based on intention to treat analysis, which is lower than in other recent studies of DAA-treated patients with chronic hepatitis or compensated cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiviral effect of DAAs is lower for patients with cirrhosis compared to patients with chronic hepatitis. 18 Among the patients with cirrhosis, patients with decompensated cirrhosis have a lower susceptibility to DAA therapy compared to those with compensated cirrhosis. 19 The SVR12 rate in this study was 85% (28 of 33 patients) based on intention to treat analysis, which is lower than in other recent studies of DAA-treated patients with chronic hepatitis or compensated cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced liver fibrosis is known to be associated with refractoriness to DAA treatment in HCV‐infected patients. The antiviral effect of DAAs is lower for patients with cirrhosis compared to patients with chronic hepatitis 18 . Among the patients with cirrhosis, patients with decompensated cirrhosis have a lower susceptibility to DAA therapy compared to those with compensated cirrhosis 19 .…”
Section: Discussionmentioning
confidence: 99%
“…26 A recent Japanese multicenter cohort study revealed an SVR rate of 90.8% in patients with high FIB-4, which was significantly lower compared to 98.1% of those with low FIB-4 after SOF+RBV therapy. 27 The reason for the universally high SVR rate in NC (97.6%) or cirrhotic (99.1%) Korean patients might be the longer treatment duration for cirrhosis compared to that of Japanese patients who were only allowed 12 weeks of treatment due to reimbursement limitations for SOF-based treatment in Japan. Moreover, four decompensated cirrhotic patients showed SVR rate of 100% without any significant adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced liver fibrosis or cirrhosis or baseline NS5A resistance-associated substitution Y93H may responsible for the failure of the virologic response, owing to its interference with responses to DAA therapy affect virological response to DAAs therapy. [ 29 , 30 ] Furthermore, SOF based pangenotypic DAAs therapy also achieved high SVR12 rate in CHC patients with hypertension or diabetes of our cohort. Another pangenotypic DAA, GLE/PIB also yield high SVR12 rates in CHC patients with HCV GT 1 to 6 with or without cirrhosis, ranging from 91% to 100%.…”
Section: Discussionmentioning
confidence: 52%